Simetria quiral: fótons, píons e núcleons - Pupin, Joel César [UNESP] (1994)
In this Work we study the role played by chiral and electromagnetic gauge symmetries, the weak constant 'g IND. A' and pion-nucleon couplings in three processes; single and double pion photo production and photon-nucleon interaction. The first two of them are treated at tree levei, whereas the last one includes one loop corrections. The role of the symmetries is analyzed considering the existence of relationships among various diagrams contributing to a given process. The influence of the way pions couple to nucleons is studied by comparing results obtained by means of the linear sigma model and the non linear model proposed by Weinberg. Finally, the role of 'g IND. A' is assessed by direct inspection of formal expressions. Our study showed that chiral symmetry is relevant only for double pion photo production. In particular, chiral symmetry does not influence the pion cloud contribution to the electromagnetic nucleon form factor, at least within the one loop approximation considered. These results pave the way for more comprehensive studies of the role of chiral symmetry in non perturbative approaches, such as the Skyrme model